Prediction of helmet use among Malaysian motorcyclist using structural equation modeling - Ambak, Kamarudin; Ismail, Rozmi; Abdullah, Riza Atiq; Borhan, Muhamad Nazri (AENSI Publishing Corporation, 2010)
In Malaysia, 50% of fatalities in road traffic accidents were from motorcycle users. Head injuries found is a major cause leading to death. Despite the safety helmet is the best protective equipment to prevent or reduce head injury, majority motorcycle user did not use or did not fasten properly. In understanding this problem, the behavioral sciences theory and engineering aspect are needed to provide better explanation and comprehensive insights into solutions. The Theory Planned Behavior (TPB) and Health Belief Model (HBM) were used in predicting the behavioral intention toward proper helmet usage among motorcyclist. Results show that the constructs variables are reliable and statistically significant with the exogenous and endogenous variables. A multivariate analysis technique, known as Structural Equation Model (SEM) was used in modeling exercise. The full structured models were proposed and tested, thus the significant predictors were identified. Finally, the TPB model with good-of-fit indices was selected as the best model in predicting motorcyclist behavioral intention toward usage of safety helmet.